A new remarkable representative of Uropodina mites from Seychelles (Acari, Mesostigmata, Trematuridae) - Jenő Kontschán; Sergey G. Ermilov (ZooKeys)
A new genus, Trematirunella gen. nov. (Mesostigmata: Uropodina: Trematuridae), with Trematirunella seychellia sp. nov. as its type species, is described, based on a female, males, and deutonymphs collected in soil samples from the Seychelle Islands. The new genus belongs to the family Trematuridae based on the shape of the corniculi, gnathosomal setae, tritosternum and chelicerae. Members of the new genus bear a preanal suture on the ventral shield, two pairs or more pairs of wide, robust and sword-like setae on the caudal part of the dorsal shield, very dense setation on the caudal area of the marginal shield and an incision on the anterior part of the dorsal shield. These characters are missing in the other genera of Trematuridae. Two previously described species (Trichouropoda lagunae Hirmatsu & Hirschmann, 1988 and Trichouropoda palawanensis Hirschmann & Hirmatsu, 1990) from the Philippines are transferred to the new genus, as Trematirunella lagunae (Hirmatsu & Hirschmann, 1988), comb. nov. and Trematirunella palawanensis (Hirschmann & Hirmatsu, 1990), comb. nov. The new species differs from its congeners in the sculptural pattern of the female genital shield and in the shape of the robust and sword-like setae on the caudal area of the dorsal shield.